2007
DOI: 10.1016/j.atmosenv.2006.10.011
|View full text |Cite
|
Sign up to set email alerts
|

C1–C8 volatile organic compounds in the atmosphere of Hong Kong: Overview of atmospheric processing and source apportionment

Abstract: We present measurements of C 1-C 8 volatile organic compounds (VOCs) at four sites ranging from urban to rural areas in Hong Kong from September 2002 to August 2003. A total of 248 ambient VOC samples were collected. As expected, the urban and suburban sites generally gave relatively high VOC levels. In contrast, the average VOC levels were the lowest in the rural area. In general, higher mixing ratios were observed during winter/spring and lower levels during summer/fall because of seasonal variations of mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
135
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(164 citation statements)
references
References 38 publications
16
135
5
2
Order By: Relevance
“…Benzene, as a carcinogenic compound forbidden to be used in industry, were mainly from automobile exhausts in urban areas [5,24,64], so dominant contribution from vehicle exhausts in the urban site GEMC explained the higher benzene/acetylene ratio than at other sites [5,28]. As toluene, C 8 -aromatics and C 9 -aromatics were widely used as solvents in painting, coating, printing and cleaning processes in the highly industrialized PRD region [3,26,33,67], their high ratios to acetylene at WQS suggested substantial contribution of AHs from industrial emissions in the upwind city of Dongguan, a worldknown manufacturing center in the region. Moreover, the ratios of toluene, C 8 -aromatics and C 9 -aromatics to acetylene at WQS were 1.24 ± 0.13, 0.68 ± 0.07 and 0.20 ± 0.03, consistent with ratios of 1.19, 0.68 and 0.22 previously reported in Dongguan, respectively [5], indicating substantial impacts of emissions from Dongguan on air pollutants occurring at WQS during fall-winter with northeast prevailing winds.…”
Section: Diagnostic Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzene, as a carcinogenic compound forbidden to be used in industry, were mainly from automobile exhausts in urban areas [5,24,64], so dominant contribution from vehicle exhausts in the urban site GEMC explained the higher benzene/acetylene ratio than at other sites [5,28]. As toluene, C 8 -aromatics and C 9 -aromatics were widely used as solvents in painting, coating, printing and cleaning processes in the highly industrialized PRD region [3,26,33,67], their high ratios to acetylene at WQS suggested substantial contribution of AHs from industrial emissions in the upwind city of Dongguan, a worldknown manufacturing center in the region. Moreover, the ratios of toluene, C 8 -aromatics and C 9 -aromatics to acetylene at WQS were 1.24 ± 0.13, 0.68 ± 0.07 and 0.20 ± 0.03, consistent with ratios of 1.19, 0.68 and 0.22 previously reported in Dongguan, respectively [5], indicating substantial impacts of emissions from Dongguan on air pollutants occurring at WQS during fall-winter with northeast prevailing winds.…”
Section: Diagnostic Ratiosmentioning
confidence: 99%
“…Nevertheless, −75% to 150% uncertainties still existed for the anthropogenic VOC emission sources [30]. Based on observed data, receptor models including principal component analysis/absolute principal component scores (PCA/APCS) [32,33] and positive matrix factorization (PMF) have been previously applied to explore VOC emission sources based on VOCs measured at four stations with different environments in Hong Kong (HK) during two sampling campaigns [34], at a Hong Kong urban site and a rural site in inland PRD during October-December 2007 [35], and at 84 sites in a grid study with four campaigns during 2008-2009 over the PRD region [36]; and in the inner PRD region sources of VOCs was apportioned by chemical mass balance (CMB) with ambient VOC data observed at fall-winter 2004 [37]. As CMB receptor model are based on the well-known source profiles [38,39], available emission source profiles in the PRD region are neither sufficient nor representative to cover the complicated emission sources in this region.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most densely populated cities in the world, Hong Kong has over 7.2 million people and more than 699 540 registered vehicles in an area of 1104 km 2 as of December 2014 (Hong Kong Transport Department, 2014). Special attention has been paid to the characteristics of roadside VOCs and their impacts on the local air quality of Hong Kong during the past years Ho et al, 2004;Guo et al, 2007;Louie et al, 2013;Ling and Guo, 2014). Previous studies have shown that vehicular emissions are one of the major contributors to ambient VOCs in Hong Kong (Guo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Special attention has been paid to the characteristics of roadside VOCs and their impacts on the local air quality of Hong Kong during the past years Ho et al, 2004;Guo et al, 2007;Louie et al, 2013;Ling and Guo, 2014). Previous studies have shown that vehicular emissions are one of the major contributors to ambient VOCs in Hong Kong (Guo et al, 2007). Lau et al (2010) found that 31-48 % of ambient VOCs in Hong Kong were generated by vehicle-and marine-vessel-related sources in [2002][2003], and the percentage increased to 40-54 % in 2006-2007. In order to investigate urban roadside VOCs in Hong Kong, multiple sampling and analytical techniques were used, such as offline 2,4-dinitrophenylhydrazine (DNPH) cartridge sampling followed by high-performance liquid chromatography (HPLC) analysis for oxygenated volatile organic compounds (OVOCs); online gas chromatography (GC) with flame ionization detection (FID); and offline canister sampling followed by GC with mass spectrometer detection (MSD), FID, and electron capture detection (ECD) for VOCs Cheng et al, 2014;Ou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the Pearl River Delta region, the speciation and sources of VOC have been studied intensively in some field measurements. For example, Guo et al (2004aGuo et al ( , b, 2006Guo et al ( , 2007 focused on source apportionment of observations of VOC using statistical analyses. Other previous studies were conducted on the ambient levels of VOC in Hong Kong (Sin et al, 2000;Ho et al, 2002;Lee et al, 2002;Wang et al, 2002Wang et al, , 2005So and Wang, 2004;Chan et al, 2006;Tang et al, 2007Tang et al, , 2008Barletta et al, 2008;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%